TNFR signalling and its clinical implications. (January 2018) - Tseng, Wen-Yi; Huang, Yi-Shu; Lin, Hsi-Hsien; Luo, Shue-Fen; McCann, Fiona; McNamee, Kay; Clanchy, Felix; Williams, Richard
Highlights: TNFR1 is ubiquitously expressed, whereas TNFR2 is expressed on a restricted range of cell types. TNFR1 and TNFR2 signalling mediate different pathophysiologic effects. TNFR2 signalling may be beneficial for autoimmune disease. Abstract: Tumour necrosis factor-α (TNF-α) is a highly pleiotropic cytokine with effects on multiple pathological and physiological functions via two distinct receptors, TNFR1 and TNFR2. Much of the pro- inflammatory action of TNF-α is mediated by TNFR1 whereas TNFR2 is thought to play an immunoregulatory and tissue protective role. Anti-TNF- α biologics have been extremely successful in treating a number of immune mediated pathologies, including rheumatoid arthritis, ankylosing spondylitis, psoriasis, psoriatic arthritis and inflammatory bowel disease. However, anti-TNF therapy has been shown to induce systemic lupus erythematosus and psoriasis in some patients, and to be deleterious in multiple sclerosis. It is hypothesized that these paradoxical effects of anti-TNF-α are due to inhibition of TNFR2 signalling. In this review, we will focus on the biology and pathophysiologic role of TNF-α and on the therapeutic implications of targeting TNF-α receptor signalling.